THE CHARACTERISTICS OF SUCCESSFUL INNOVATION FOR POVERTY ALLEVATION IN TERE LIYE'S SI ANAK KUAT - Tirmidi Tirmidi; Arofi Halim; Maulana Rizaldi (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
In many cases in Indonesian rural area, innovation is one of key words for poverty alleviation. The novel Si Anak Kuat by Tere Liye describes how an innovation becomes a option to alleviate poverty in rural areas on the island of Sumatra and how Amelia, the main character in this novel, carries out innovation diffusion steps. Through discourse analysis, this research aims at revealing the characteristics of diffusion of innovation implemented in Tere Liye's Si Anak Kuat that cause the innovation, in this case is substituting old coffee plants with new and high quality one, can be accepted by all villagers. The results show that the innovation in the novel comes into its acceptance to all villagers due to its highly economical relative advantages, its highly compatibility, triability, and also its observability. The innovation is also supported by its hardly complexity.